Serum homocysteine level, vitamin B12 levels, and erythrocyte folate in psoriasis: A case-control study - Robabeh Abedini, MD; Azadeh Goodarzi, MD; V. Saeidi, MD; Seyedeh H. Hosseini, MD; Atefeh Jadidnuri, MD; Mehrnaz Salehi Taleghani, MD; Vahide Lajevardi, MD (Wolters Kluwer, 2019)
Background: One of the most important organ involvements in psoriasis is atherosclerotic cardiovascular disease. Homocysteine is known to have atherogenic properties, but some inconsistency exists in the literature about its probable role as a risk factor of cardiovascular disorder in patients with psoriasis. Objective: Because of some controversies, we compared homocysteine levels and related parameters of metabolic cycles in patients with psoriasis and healthy individuals. Methods: This case-control study was conducted on 50 patients with psoriasis and 50 healthy individuals as the controls. Serum homocysteine, vitamin B12 levels, and erythrocyte folate concentrations were checked in all participants. Results: Mean serum homocysteine, erythrocyte folate, and vitamin B12 levels did not show any significant difference between the two groups (p > .05), but interestingly, in patients with psoriasis, men had a significantly higher incidence of hyperhomocysteinemia and lower levels of erythrocyte folate (p = .14). Overall, there is no significant difference in serum levels of homocysteine and metabolic-related parameters between the case and control group. There was no significant relationship between the severity of psoriasis and the body mass index of patients (p > .05). Conclusion: Patients with psoriasis had a higher body mass index and higher levels of homocysteine in men. Hyperhomocysteinemia could be a predisposing factor of cardiovascular events, but more evaluations as a part of metabolic syndrome in patients with psoriasis are needed. Keywords: Homocysteine, erythrocyte (RBC) folate, vitamin B12, psoriasis